Analysis of Inspection Scheduling on Free Spanning Subsea Pipeline Using Risk Based Inspection (RBI) Method - Daniel Mohammad Rosyid; Abizar Giffari; Yoyok Setyo Hadiwidodo (DRPM (Direktorat Riset dan Pengabdian kepada Masyarakat) ITS, 2020)
The subsea pipeline system of PT. X located at north of West Java transports natural gas with 19 kilometers long and 16 inches standard pipe size. The rough seabed causes free span problem. The system will be threatened by a structural failure of fatigue due to Vortex Induced Vibration (VIV) and local buckling as the effects of free span. In this Final Project, a total of 136 free spans on subsea pipeline system due to the uneven seabed are analyzed. The screening will be done for spans with length and diameter ratio more than 30 to figure out the free span which pass the screening and know the risk level of the subsea pipeline due to free span. The result for fatigue screening due to VIV, spans with a length more than 25 meters did not pass the screening. Local buckling occurred at the longest free span with a length of 62 meters. The level of risk to structural failure caused fatigue due to VIV has the highest level in terms of business and the environment, namely in the medium category. The level of risk to local buckling failures for safety, environmental, and business terms was in low category.